2021
DOI: 10.1515/biol-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the SPL gene family in five Rosaceae species: Fragaria vesca, Malus domestica, Prunus persica, Rubus occidentalis, and Pyrus pyrifolia

Abstract: SQUAMOSA promoter-binding protein-like (SPL) transcription factors are very important for the plant growth and development. Here 15 RoSPLs were identified in Rubus occidentalis. The conserved domains and motifs, phylogenetic relationships, posttranscriptional regulation, and physiological function of the 92 SPL family genes in Fragaria vesca, Malus domestica, Prunus persica, R. occidentalis, and Pyrus pyrifolia were analyzed. Sequence alignment and phylogenetic analysis showed the SPL proteins had sequence con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
4
0
1
Order By: Relevance
“…The results showed that the SPL members had the SBP domain, which comprised two non-interleaved zinc finger-like structures (Zn-1/2) and one NLS motif (Supplementary Figures 1c, 2). Based on the alignments of the Ipomoea SPLs, the Zn-2 motif showed higher conservation than the Zn-1 and NLS motifs, which was consistent with the results in Rosaceae (Jiang et al, 2021) and Oryza species (Zhong et al, 2019; Supplementary Figure 2). The Zn-2 motif in all Ipomoea SPLs was a Cys-Cys-His-Cys (C2HC) type (except IbSPL23) whereas the Zn-1 motif showed varied types: Cys-Cys-Cys-Cys (C4) type in clade I and Cys-Cys-Cys-His (C3H) type in the remaining clades.…”
Section: Gene and Protein Structure Of The Ipomoea Squamosa Promoter-...supporting
confidence: 86%
“…The results showed that the SPL members had the SBP domain, which comprised two non-interleaved zinc finger-like structures (Zn-1/2) and one NLS motif (Supplementary Figures 1c, 2). Based on the alignments of the Ipomoea SPLs, the Zn-2 motif showed higher conservation than the Zn-1 and NLS motifs, which was consistent with the results in Rosaceae (Jiang et al, 2021) and Oryza species (Zhong et al, 2019; Supplementary Figure 2). The Zn-2 motif in all Ipomoea SPLs was a Cys-Cys-His-Cys (C2HC) type (except IbSPL23) whereas the Zn-1 motif showed varied types: Cys-Cys-Cys-Cys (C4) type in clade I and Cys-Cys-Cys-His (C3H) type in the remaining clades.…”
Section: Gene and Protein Structure Of The Ipomoea Squamosa Promoter-...supporting
confidence: 86%
“…The results showed that all of the SPL members had the SBP domain, which was composed of two non-interleaved zinc nger-like structures (Zn-1/2) and one nuclear localization signal (NLS) motif (Figure 3b, Supplementary Figure S1). Based on the alignments, the Zn-2 motif is more conserved than the Zn-1 and NLS motif in all Ipomoea SPLs analyzed, which was also observed in Rosaceae [30] and Oryza species [31] (Supplementary Figure S1). For example, the Zn-2 motif in all Ipomoea SPLs was a Cys-Cys-His-Cys (C2HC) type (except IbSPL23); and the Zn-1 motif showed different signatures, which was Cys-Cys-Cys-Cys (C4) type in clade I and Cys-Cys-Cys-His (C3H) type in the remaining clades.…”
Section: Gene and Protein Structure Of The Ipomoea Spl Familymentioning
confidence: 76%
“…The QTL qSC 8 associated with Striga emergence count was found to be linked with the gene model, GRMZM2G371033, SBP-transcription factor. The SBP-transcription factors are very important for plant growth, development, and defense response as they regulate the specific downstream gene expression, such as the phase transition from vegetative to reproductive stage, leaf development, plant hormone signaling, toxin resistance, copper deficiency response, temperature, and drought stress tolerance ( Jiang et al, 2021 ). The gene model GRMZM2G075715, ARF-transcription factor was associated with the QTL qSC 7 identified for Striga emergence count.…”
Section: Discussionmentioning
confidence: 99%